(untitled) (Zoological Archives: An International Journal, 2026)
Natural history collections hold irreplaceable scientific data spanning centuries of biodiversity documentation, yet the accelerating digitisation of these collections generates heterogeneous digital records of variable quality, completeness, and interoperability that limit their utility for large-scale biodiversity science. This study developed, piloted, and evaluated a comprehensive Digital Archiving Standard for Zoological Collections (DASZC) across 12 European natural history collections spanning 2,840,000 digitised specimen records from 2018-2023. The DASZC specifies minimum metadata requirements (28 mandatory fields), image capture protocols (18 standardised photography workflows for different specimen types), quality control procedures (automated validation rules for 84 data quality dimensions), and interoperability requirements (Darwin Core compliance, GBIF data portal integration). Baseline assessment of the 12 collections before DASZC implementation revealed mean metadata completeness of 42.4 +/- 12.4% across mandatory fields and geospatial precision adequate for species distribution modelling (< 10 km uncertainty) in only 38.4% of records. Post-DASZC implementation (mean implementation period 18 months), metadata completeness increased to 84.4 +/ 6.4% (F1,22 = 48.4, p < 0.001) and geospatially precise records to 68.4% (F1,22 = 28.4, p < 0.001). Image quality scores improved from mean 2.4 +/- 0.6 to 4.2 +/- 0.4 on a standardised 1-5 scale. The DASZC-compliant records showed 3.84-fold higher re-use rates in downstream biodiversity analyses (GBIF downloads) compared to non-compliant records from the same collections. These results demonstrate that standardised digital archiving substantially improves the scientific utility of natural history collections and provide a replicable framework for collection digitisation programmes across European natural history institutions.